Recent advances in microfiber sensors for highly sensitive biochemical detection. (16th September 2019) - Li, Yanpeng; Xu, Zhilin; Tan, Shijie; Fang, Fang; Yang, Liuyang; Yuan, Botai; Sun, Qizhen
Abstract: Highly sensitive biochemical sensors have acquired paramount importance in the fields of medical diagnosis, environmental monitoring and food safety control, etc. Optical microfiber with sub-wavelength diameter has become an essential platform for exploring fiber-optic biochemical sensors on micro-scale, due to the advantages of compact size, large evanescent field and high optical nonlinearity. In this article, recent advances in microfiber biochemical sensors are reviewed. It begins with the fabrication methods of the microfiber, focusing mostly on the microfiber made from silica. The microfiber structures are roughly classified as optical intensity-modulated sensors and optical phase-modulated sensors according to the demodulation approaches. The fundamental sensing mechanisms of the microfiber structures are explained. This is followed by an overview of microfiber sensors for biochemical detection. The overview is classified into four application areas including biosensors, gas sensors, sensors for non-gaseous chemicals and sensors for environmental parameters. Finally, we conclude the paper with an outlook on challenges and opportunities for microfiber biochemical sensors.